Comparative Study on Prediction of the Girths of Young Females' Body (Journal of Fiber Bioengineering and Informatics, 2018)
To compare the advantages and disadvantages of the measurement and girth fitting methodsof human body, in this paper, 248 female students were selected as subjects. Frontal and profile imagesof human body were taken by digital camera. The width, the whole thickness, the front segmentthickness and back segment thickness of cross-sections at chest, waist, abdomen and hip were measuredby photogrammetric measurement. The curve consisted of two-elliptic arcs and BP (Back-Propagation)Neural Network were employed to model chest girth, waist girth, abdomen girth and hip girth based onthe measured data, and the girths were obtained respectively. These two methods were compared in thispaper.